The limited effectiveness of sanctions on Russia: Modeling loopholes and workarounds - Michael Funke; Adrian Wende (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
Following Russia's invasion of Ukraine in February 2022, the US, EU, and likeminded countries swiftly imposed an expanded set of primary and secondary export restrictions on Russia. This paper assesses the effectiveness of those measures and their ongoing refinement and modification over time using a calibrated three-country dynamic general equilibrium trade model with heterogeneous firm productivities. The modeling set-up comprises a rich specification of export ban loopholes and workarounds, as well as subsequent countermeasures such as re-exports, ghost trade, and secondary extraterritorial export bans. The numerical model evaluations and the numerous policy counterfactuals highlight the challenges of export ban evasion and offer insights for effective export ban designs in the future. We show that targeted secondary extraterritorial export bans have proven an impactful policy tool in diminishing Russia's imports of critical technologies.
urn:nbn:fi-fe2025051947380
Keywords: F12; F13; F51; H56; 330; Russia; export bans; sanctions evasion; quantitative trade model